One Pot Synthesis of 3,9-Bis-(2,4-di-tert-butyl phenoxy)-2,4,8,10-tetraoxa-3,9-diphospha-spiro[5.5]undecane, their Chalcogenides and Metal Complexes - Rani, Manju; Kumar Shukla, Davender; Ali Khan, Arif (Asian Journal of Chemistry, 2013)
A simple method for the synthesis of 3,9-di[2,4-di-tert-butyl phenoxy]-2,4,8,10-tetraoxa-3,9-diphospha-spiro[5.5]undecane and its chalcogenides and metal complex are reported.